2021
DOI: 10.1155/2021/4874757
|View full text |Cite
|
Sign up to set email alerts
|

Wind Speed Forecast Based on the LSTM Neural Network Optimized by the Firework Algorithm

Abstract: Wind energy is a renewable energy source with great development potential, and a reliable and accurate prediction of wind speed is the basis for the effective utilization of wind energy. Aiming at hyperparameter optimization in a combined forecasting method, a wind speed prediction model based on the long short-term memory (LSTM) neural network optimized by the firework algorithm (FWA) is proposed. Focusing on the real-time sudden change and dependence of wind speed data, a wind speed prediction model based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Hyperparameter tuning is a paramount aspect of ML and has been tested in the context of wind power forecasting using metaheuristic algorithms. Previous works (Shao et al 2021) proposed a firework algorithm-based approach to optimize hyperparameters of LSTM neural networks for wind power forecasting. The authors demonstrated that the proposed approach achieved higher forecasting accuracy compared to other optimization techniques, indicating the importance of hyperparameter tuning for accurate wind power forecasting.…”
Section: Overview Of Research Background and Literature Reviewmentioning
confidence: 99%
“…Hyperparameter tuning is a paramount aspect of ML and has been tested in the context of wind power forecasting using metaheuristic algorithms. Previous works (Shao et al 2021) proposed a firework algorithm-based approach to optimize hyperparameters of LSTM neural networks for wind power forecasting. The authors demonstrated that the proposed approach achieved higher forecasting accuracy compared to other optimization techniques, indicating the importance of hyperparameter tuning for accurate wind power forecasting.…”
Section: Overview Of Research Background and Literature Reviewmentioning
confidence: 99%
“…A neural network approach can also be used in the prediction of the stochastic time series. In study [25], a firework long short-term memory network is proposed for wind speed prediction. Considering the non-stationary characteristics of the sea wave, empirical mode decomposition is employed as the data preprocessing technique for the long shortterm memory network (EMD-LSTM) in [26].…”
Section: Literature Review For the Stochastic Time Series Predictionmentioning
confidence: 99%
“…LSTM is a powerful timeseries prediction algorithm used for genetics [23], windpower prediction [24,25], text processing [26], and human action prediction.…”
Section: Lstmmentioning
confidence: 99%